The Role of the Secretariat of the Regional House of Representatives in the Implementation of the Duties and Functions of the Regional House of Representatives of Situbondo Regency - Fariz Anggara; Ika Devy Pramudiana; Eny Haryati; Sapto Pramono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze the role of the Secretariat of the Regional House of Representatives and the factors that affect the role of the Secretariat of the Regional House of Representatives in the implementation of the duties and functions of the Regional House of Representatives of Situbondo Regency. The data analysis technique in the study uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study showed. The Role of the DPRD Secretariat in the Implementation of Secretariat Administration and Financial Administration. The role of the Situbondo Regency DPRD Secretariat in the formulation of Regional Regulations that can control political dynamics. The Secretariat of the Regency DPRD carries out its role in providing facilitation for the running of the session or meeting. The role of the DPRD Secretariat is to provide and coordinate the experts needed by the DPRD in carrying out its functions according to needs. The Secretariat of the Situbondo Regency DPRD facilitates all the needs and needs of DPRD Members in carrying out their functions: one of them is in the field of Legislation. Factors that affect the role of the Secretariat of the House of Representatives include leadership factors. The leader or head of the SKPD of the Secretariat of the Sutubondo Regency DPRD in leading and carrying out service activities, applying an instructional, consultative and participatory leadership style. The discipline factor is a factor that affects the success or becomes a factor that hinders the role of the Situbondo Regency DPRD Secretariat. The discipline factor applied in the DPRD Secretariat is in the form of accuracy and responsibility in carrying out secretarial duties. The human resources owned by the Secretariat have been very supportive, both work experience and the number of employees. The available human resources will certainly affect the organization such as services and improving the performance of the Situbondo Regency DPRD Secretariat